Three dimensional culture of fresh and vitrified mouse pre-antral follicles in a hyaluronan-based hydrogel: a preliminary investigation of a novel biomaterial for in vitro follicle maturation - Desai Nina; Abdelhafez Faten; Calabro Anthony; Falcone Tommaso (BMC, 2012)
Abstract Background Folliculogenesis within the ovary requires interaction between somatic cell components and the oocyte. Maintenance of 3-dimensional (3-D) architecture and granulosa-oocyte interaction may be critical for successful in vitro maturation of follicles. Testing of novel biomaterials for the 3-D culture of follicles may ultimately lead to a culture model that can support the longer in vitro culture intervals needed for in vitro maturation of human oocytes from ovarian tissue biopsies. Methods A novel tyramine-based hyaluronan (HA) hydrogel was tested for its biocompatibility with ovarian follicles. The HA was prepared at concentrations from 2 to 5 mg/ml. HA hydrogel was also formulated and tested with matrix proteins (ECM). Enzymatically isolated pre-antral follicles from the ovaries of 10-12 day SJL pups were divided amongst control (CT) and HA treatments. The growth of both fresh and vitrified follicles was assessed after encapsulation in the hydrogel. The basal culture medium was MEM alpha supplemented with FSH, LH, ITS and 5% FBS. Maturation was triggered by addition of hCG and EGF after in vitro culture (IVC). Outcome parameters monitored were follicle morphology, survival after IVC, antrum formation, GVBD and MII formation. Differences between treatments were analyzed. Results HA and ECM-HA encapsulated follicles looked healthy and maintained their 3-D architecture during IVC. In control cultures, the follicles flattened and granulosa:oocyte connections appeared fragile. Estradiol secretion per follicle was significantly higher by Day 12 in ECM-HA compared to HA or CT (4119, 703 and 1080 pg/ml, respectively). HA and ECM-HA cultured follicles had similar survival rates (62% and 54%, respectively), percent GV breakdown (96-97%), MII formation (47-48%) and oocyte diameters at the end of IVC. Control cultures differed significantly in percent GVBD (85%) and MII formation (67%) . Vitrified-warmed follicles encapsulated in HA had an oocyte maturation rate to MII of 54% as compared to 57% in non-embedded follicles. Conclusions Initial testing of this new and unique HA-based hydrogel was quite promising. The ease of follicle encapsulation in HA, its optical transparency and ability to be molded combined with its support of follicle growth, estradiol secretion and resumption of meiosis make this HA-hydrogel particularly attractive as model for 3-D ovarian follicle culture.